EKSPLORASI ELEMEN INTEGRATED REPORTING DALAM ANNUAL REPORTS PERUSAHAAN DI INDONESIA - Chariri, Anis; Januarti, Indira (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study aims to identify the patterns and scope of integrated reporting and to examine the effect of audit committee characteristics (expertise and meeting) on elements of integrated reporting disclosed in the annual report of companies listed on the Indonesia Stock Exchanges (IDX). This study used 170 annual reports of companiesÃ‚Â listed on the IDX as research data (not all companies have the required data). Research data were then analyzed using STATA / MP14 Software. The findings showed that the IDX-listed companies have presented annual reports in accordance with the elements of integated reporting although the scope of presentation was relatively low amounting of Ã‚Â 51% (33 of 64 indicators). Furthermore, this study revealed that the audit committeesÃ¢â‚¬â„¢ expertise (in accounting/ finance) and the frequency of audit committee meetings positively and significantly influenced the scope of the integrated reporting presented in the annual report of the companies.